Laparoscopy-assisted endoscopic full-thickness resection of gastric subepithelial tumors using a nonexposure technique - Goto, Osamu; Takeuchi, Hiroya; Sasaki, Motoki; Kawakubo, Hirofumi; Akimoto, Teppei; Fujimoto, Ai; Ochiai, Yasutoshi; Maehata, Tadateru; Nishizawa, Toshihiro; Kitagawa, Yuko; Yahagi, Naohisa (Endoscopy, 2016)
Background and study aims: To avoid bacterial contamination and tumor seeding during gastrectomy surgery, we developed a nonexposure technique for endoscopic full-thickness resection with laparoscopic assistance. The feasibility and safety of nonexposed endoscopic wall-inversion surgery (NEWS) for gastric subepithelial tumors (SETs) were investigated.Patients and methods: For protruding gastric SETs ≤ 3 cm in diameter, NEWS was performed in the following sequence: laparoscopic seromuscular incision after endoscopic submucosal injection, laparoscopic seromuscular suturing with the lesion inverted, endoscopic mucosal and submucosal incision, and transoral retrieval. Technical outcomes and postoperative courses were investigated.Results: In all 20 consecutive cases, including six SETs with ulceration, NEWS was completed (mean procedural time, 213.5 minutes) without severe intraoperative or postoperative adverse events. R0 resection and perforation rates were 100 % and 5.0 %, respectively. During the mean observational period of 10.1 months, all patients survived without recurrence or apparent discomfort during food intake.Conclusion: NEWS for gastric SETs was feasible and safe and represents a useful option for minimally invasive local resection even in cases of SETs with ulceration or cancers.